DISTRIBUTION AND DIET COMPOSITION OF TWO SYMPATRIC MONGOOSE SPECIES IN MURREE KAHUTA KOTLI SATTIAN NATIONAL PARK, PAKISTAN. - R. Khatoon; A. Anwar; S. Khalil; U. Habiba (Journal of Animal and Plant Sciences, 2022)
Understanding the distribution and diet of carnivore is important to consider ecological role of species. As food is a critical resource for carnivore predators and its partitioning among sympatric species is crucial for their coexistence. The current study aimed at exploring distribution, diet composition, and diet breadth, niche overlap among two sympatric mongoose species occurring in Murree Kahuta Kotli Sattian National Park (MKKNP). 82 fecal samples were collected from 23 sites and recognized to species inside field based on morphology, odor, and extra signs. Presence signs of both species recorded from 23 survey sites. However, field diagnosis of small Indian Mongoose and Indian grey mongoose indicated presence at 12 and 14 sites, respectively. Fourteen dietary items were recovered in diet of small Indian mongoose i.e rodents, plant matter, insects and reptiles. The diet of Indian grey mongoose also comprised of (15) dietary items. Among both sympatric carnivores overall dietary breadth of Indian grey mongoose is narrow (BA = 0.5). as compared to small Indian mongoose (BA = 0.6). Moderate overlap was found between both mongoose species (0.62)
Keywords: Small Indian mongoose; Indian Grey mongoose; Seasonal variation; Dietary breadth; Niche overlap